Use of Digital Learning Resources in History Subjects Class XI of SMA Negeri 10 Banjarmasin - Rauni, Rauni; Heri Susanto; Melisa Prawitasari (JURNAL PENDIDIKAN IPS, 2024)
Learning resources are one of three important components in the learning process, namely students, teachers and learning resources. Success in the learning process depends on the use of selected learning resources and media. This research focuses on history learning for class XI IPS. The aim of the research is to analyze the use of digital sources as learning resources in history lessons at SMA Negeri 10 Banjarmasin. This research uses a qualitative descriptive research method. Data collection techniques were carried out using observation, interviews and document studies related to teaching modules, photos and learning resources. The results of the research show that learning history using digital sources at SMA Negeri 10 Banjarmasin is implementing learning in class via laptop and LCD devices as a means of providing material by the teacher to students via power points, pictures and explanations of the material presented by the teacher in class. The use of digital sources in class XI history learning has been implemented at this school. There are several digital sources that students use in carrying out the learning process, such as YouTube, e-books, and the internet by accessing Google search via the website.